2005
DOI: 10.1016/j.cub.2005.02.017
|View full text |Cite
|
Sign up to set email alerts
|

The early extra petals1 Mutant Uncovers a Role for MicroRNA miR164c in Regulating Petal Number in Arabidopsis

Abstract: The data presented in this study indicate that closely related miRNA family members that are predicted to target the same set of genes can have different functions during development, possibly because of nonoverlapping expression patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
301
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(319 citation statements)
references
References 51 publications
14
301
0
4
Order By: Relevance
“…In inflorescences, miR164 targets CUC1/2 to regulate the establishment and maintenance of the shoot apical and axillary meristems and floral boundary formation (Laufs et al 2004; Mallory et al 2004; Baker et al 2005), whereas in root miR164 targets NAC1 to downregulate auxin signals for lateral root development (Guo et al 2005). Our sRNA sequencing and northern blot results confirmed that miR164 can be induced by V592-infection.…”
Section: Discussionmentioning
confidence: 99%
“…In inflorescences, miR164 targets CUC1/2 to regulate the establishment and maintenance of the shoot apical and axillary meristems and floral boundary formation (Laufs et al 2004; Mallory et al 2004; Baker et al 2005), whereas in root miR164 targets NAC1 to downregulate auxin signals for lateral root development (Guo et al 2005). Our sRNA sequencing and northern blot results confirmed that miR164 can be induced by V592-infection.…”
Section: Discussionmentioning
confidence: 99%
“…In animals, transcription studies of let-7 in C. elegans demonstrated that the temporal regulatory element (TRE) located at about 1200 nt upstream from the mature let-7 coding sequence was required for temporal upregulation of let-7 [45]. Recently, studies of the At-miR164 family showed that At-MIR164a and AtMIR164b participate in lateral root development [46], whereas At-MIR164c was demonstrated to control petal number in early flowers [47], indicating the nonredundant expression of the three members.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have uncovered the role of microRNAs (miRNAs), ~21-nucleotide noncoding RNAs, as regulators of floral patterning gene expression in Arabidopsis flower development (Aukerman and Sakai 2003;Schmid et al 2003;Achard et al 2004;Chen 2004;Mallory et al 2004a;Baker et al 2005;Millar and Gubler 2005). Plant miRNAs regulate cognate protein coding RNAs through either transcript cleavage or translational inhibition or both (reviewed in Bartel and Bartel 2003;Carrington and Ambros 2003;Bartel 2004;Dugas and Bartel 2004;He and Hannon 2004;Mallory and Vaucheret 2004;Kidner and Martienssen 2005;Chen 2005;Valencia-Sanchez et al 2006).…”
Section: Introductionmentioning
confidence: 99%